COERCION AND NON-STATE LAW (Società e diritti, 2019)
The aim of this paper is to introduce some elements of a research project in legal philosophy.Its goal is to identify some crucial topics for the definition of law.In the first part (§§ 1 & 2) I analyse some methodological difficulties of the dominant researchon the definition of law. In the second part (§§ 3 & 4) I refer to some current development oflaw and sketch some characteristics of the object to be defined, corresponding to what can becalled the process of law differentiation. In the last part of this contribute I try to sum up someelements to be taken in account in the definition of a differentiated law.Key words: Differentiation of law, Legal pluralism, Justice